A low cost and flexible carbon nanotube pH sensor fabricated using aerosol jet technology for live cell applications - Goh, Guo Liang (2019)
Minute pH changes impact all living organisms, and thus facile pH monitoring in environment and onthe cellular level is important. A low cost and flexible carbon nanotube based pH sensor is fabricated inthis work using Aerosol jet printing technique. The chemiresistive pH sensor is fabricated with a CNT-based miniaturized serpentine sensing element printed on top of the silver electrodes. The trace width ofthe serpentine sensing element is accurately controlled to about the same size as the gaps between thetraces. Aerosol jet parameters are optimized to achieve high resolution printing of 20 m. The fabricatedpH sensor shows good sensitivity (up to 59 k /pH) and repeatability (coefficient of variance <1.15%)with a response time of 20 s the sensor demonstrates excellent biocompatibility required for live cellapplications.